Dose site reactions and related findings after vaccine administration in safety studies. Issue 8 (10th March 2016) - Baldrick, Paul
Abstract: Potential new human vaccines undergo toxicology testing to evaluate local reactogenicity and systemic toxicity. A review of 30 recently published and in‐house repeat dose toxicity studies with a variety of vaccines was performed. Species tested were generally rat or rabbit, usually by intramuscular (although occasionally subcutaneous) injection. Results showed no unexpected findings indicating vaccine toxicity, but classic signs of enhanced acute and/or chronic inflammation at the dose site compared with that seen in injected control animals, often accompanied by changes in draining lymph nodes and the spleen (lymphoid hyperplasia and/or increased weight). Other associated signs of a response to vaccine dosing were altered clinical pathology parameters (commonly raised blood neutrophil count and altered globulin level). No obvious difference in dose site or systemic reaction was seen across vaccine, species or the dose route used. A non‐dose recovery period of 2 to 4 weeks was sufficient to show evidence of reversibility of dose site effects. Injection site, lymphoid tissue and clinical pathological changes can be interpreted as related to an expected reaction after vaccine dosing, with generation of an immune response largely as a result of the presence of adjuvant, although direct vaccine antigen involvement was also occasionally demonstrated by the presence of a slightly increased inflammatory response seen over adjuvant treatment only. Overall, the need for toxicity testing of vaccines is in line with current regulatory guideline requirements and has proven to be a valuable part of the safety evaluation process prior to human use. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A review of 30 recently published and in‐house repeat dose toxicity studies with a variety of vaccines was performed. Results indicated no unexpected findings indicating vaccine toxicity, but classic signs of enhanced acute and/or chronic inflammation at the dose site compared with that seen in injected control animals, often accompanied by changes in draining lymph nodes and the spleen (lymphoid hyperplasia and/or increased weight). Other associated signs of a response to vaccine dosing were altered clinical pathology parameters (commonly raised blood neutrophil count and altered globulin level).